The Influence of Leader-Member Exchange and Perceived Organizational Support on Lecturer Job Performance: Psychological Stress as a Mediator and Organizational Commitment as a Moderator - Ade Wahyudi; Dewi Trirahayu; Indra Ade Irawan; Anton Kurniawan; Amelia Ayu Marchella (Journal of Creative Power and Ambition (JCPA), 2026)
This study aims to examine the effects of Leader-Member Exchange and Perceived Organizational Support on the Job Performance of lecturers at private higher education institutions in DKI Jakarta, with Psychological Stress as a mediator and Organizational Commitment as a moderator. The study is motivated by the increasing work demands faced by lecturers in teaching, scientific publication, accreditation, community service, academic administration, and adaptation to digital systems. This research employed an explanatory quantitative approach with a survey design. The sample consisted of 200 private university lecturers selected through convenience sampling, with the criterion that respondents were active lecturers at private higher education institutions in DKI Jakarta. Data were collected using a five-point Likert scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling. The research model comprised five main constructs, one interaction term, and 39 indicators. The measurement model evaluation showed that all indicators met the criteria for convergent validity, construct reliability, and discriminant validity. The R Square values were 0.388 for Psychological Stress and 0.622 for Job Performance. The structural model testing indicated that Psychological Stress, Leader-Member Exchange, and Perceived Organizational Support had positive effects on Job Performance. Leader-Member Exchange and Perceived Organizational Support also had positive effects on Psychological Stress. Psychological Stress was found to mediate the effects of Leader-Member Exchange and Perceived Organizational Support on Job Performance. Organizational Commitment did not moderate the relationship between Psychological Stress and Job Performance, but it remained significant as a direct predictor. This study recommends strengthening academic leadership, organizational support, and productive work stress management to improve lecturer performance..